P085 Body composition effects of High Intensity Functional Exercise training during rapid weight loss in obese patients with obstructive sleep apnoea: A pilot randomised controlled trial. (7th October 2021) - Lowrie, F; Phillips, C; Yee, B; Gordon, C; Marshall, N; Cayanan, E
Abstract: Introduction: While Very Low Energy Diets (VLEDs) have been proven to reduce weight in patients with obstructive sleep apnoea (OSA) and co-morbid obesity, they can also result in excessive loss of muscle mass which adversely impacts health. Concurrent exercise training is considered an effective method of preventing muscle mass loss. Methods: This prospective randomised controlled trial will recruit 30 overweight and obese men with untreated moderate-to-severe OSA to undergo a 12-week VLED with or without high-intensity functional exercise (HIFE) training. HIFE will be delivered through a commercially available supervised exercise program and incorporates interval training with a combination of progressively graded aerobic and anaerobic exercise. The primary outcome measures are changes in body composition, assessed by dual x-ray absorptiometry (DEXA), and OSA severity (measured by apnoea hypopnea index). Secondary outcomes include glucose tolerance, ventilatory response, and peak oxygen uptake. Data will be analysed on an intention-to-treat basis. Paired T-tests will be used to test the treatment effect of exercise compared to control. Confidence intervals will be used to analyse change in muscle mass and other secondary outcomes. Results: Only one participant has completed the protocol to date. No results are available at this time. Discussion: The results of this pilot study will look to confirm whether HIFE can protect against muscle mass loss, and additively benefit OSA severity during VLED, compared to VLED alone. It will also inform estimation of feasibility for a larger definitive study.